ENFORCEMENT OF ENVIRONMENTAL CRIMINAL LAW FROM THE PERSPECTIVE OF THE UUPPLH IN INDONESIA - Putri, Salsabila Raka (Communale Journal, 2025)
The aspect of environmental punishment is a key that must be considered in the enforcement of environmental laws in Indonesia. Based on the definition, environmental crime is polluting and damaging the environment, as regulated in the Law on Environmental Protection and Management (UUPPLH). In this life, there are many violations that occur in the environmental sector that will have an impact on the life to come. To minimize the violations that occur, the government has enacted Law no. 32 of 2009 concerning Protection and Management of the Environment. By enacting this law, it is hoped that it can run in accordance with the problems that occur today. For research in this writing, using normative research methods, which are based on written regulations, literature study that examines aspects of theory, and legal explanations. In Indonesia, the main factor that causes the stipulated regulations to not work well is the lack of awareness of related parties about the importance of preserving nature and the environment. Andthe results of this study indicate that environmental law enforcement in Indonesia is based on a criminal law perspectivestudy